(untitled) (MEDIEVAL HISTORY OF CENTRAL EURASIA, 2024)
Abstract. It is analyzed in an article the findings of several bone arrows’ tips, that were detected in the course of excavations during the year 2007 at the monument Ulug-Choltuh, that is located in the valley of Edigan River, right-hand-side tributary of Katun River in the territory of the Altai Mountains. It was researched at the monument over the course of this field season the several burial grounds with male entombments, where it was the bows’ bone side plates as well as the iron bone arrows’ tips as a part of accompanying equipment. It is traced and analyzed in the article the principal results of previous research of similar arrows’ tips from the monuments of the second quarter of the 1 stmillennium A.D. in the territory of Altai Mountains. Bone arrows’ tips from excavations of the monument Ulug-Choktuh were considered and classified on formal signs to sections, groups and types. It was singled out two sections among the bone tips to approach of haft element: pivot arrows and tips with forked haft element. It was determined among such arrows the several groups of tips with trilateral and rhombic section of feather. Within the singled out groups it was as well as singled out some autonomous arrows’ types, which differ from each other to from of feather. It was traced several positioning specificities of bone and iron arrows’ tips in sepulchral pits as a part of excavated male burial places, researched in the course of field season 2007 at the monument Ulug-Choltuh. It is pointed out that the bone arrows were put into burial places in that same locations as the iron arrows’ tips.